MHD instability at the cathode spot as the origin of the vortex formation in high-intensity plasma arcs. (24th January 2022) - Barati, Hadi; Kharicha, Abdellah; Al-Nasser, Mohamad; Kreuzer, Daniel; Hackl, Gernot; Gruber, Markus; Ishmurzin, Anton; Redl, Christian; Teplyakov, Igor O; Wu, Menghuai; Ludwig, Andreas
Abstract: Magnetohydrodynamic instability in a high-intensity arc, similar to typical arcs in DC electric arc furnaces, is simulated using an induction based model under 2D axisymmetric conditions. Time-averaged results show a good agreement with steady-state calculated results expected for a stable arc. The transient results declare that z-pinch close to the cathode, occurring due to the high electrical current density, is responsible for arc instability in this region. The unstable behavior of the arc can be evaluated in a periodic procedure. Moreover, correlations between the fluctuations in total voltage drop curve and the arc shape are investigated: when the arc is in form of column (or bell) the total voltage drop is on a minimum peak; if there is an irregular expansion of the arc in form of arms, the total voltage drop shows a maximum peak.